Design of Stapled Peptide Ligands of GABARAP to Inhibit Autophagy - Brown, Hawley F. (Tufts Archival Research Center, 2020)
Autophagy is a process in which cells recycle damaged or unnecessary proteins and organelles to use for maintenance and growth. This process is important for cellular health, but when dysregulated, it is implicated in many diseases. For example, in some aggressive, late-stage cancers, cells become “autophagy addicted,” and rely heavily on autophagy as a housekeeping process and to provide the biomolecules necessary to continue unregulated growth. Therefore, inhibiting autophagy can be therapeutic in these cells by interrupting this process. While several autophagy inhibitors currently exist, their lack of specificity limits their usefulness. For research and therapeutic applications, a potent, specific, and cell-penetrant autophagy inhibitor is required. GABAA receptor associated protein (GABARAP) is an adaptor protein required for autophagy to occur. In this project, we developed stapled peptide ligands of GABARAP based on the K1 peptide reported by Weiergräber et al.. We used diversity-oriented stapling to develop peptides with high affinity and selectivity for GABARAP, as well as a peptide with high affinity to both GABARAP and LC3B. This work represents the first stapled peptide inhibitors of GABARAP and among the tightest binding ligands to GABARAP and LC3B. This research informs work on determinants of GABARAP affinity and specificity, and the peptides developed represent promising starting points for further development of specific autophagy inhibitors.